Association between circulating microRNA-126 expression level and tumour necrosis factor alpha in healthy smokers. (4th July 2019) - Elfiky, Asmaa M.; Ahmed Mahmoud, Asmaa; Zeidan, Hala M.; Mostafa Soliman, Mohamed
Abstract: Introduction: Smoking contributes to the death of a million people worldwide each year. Smokers experience an alteration in tumour necrosis factor-alpha (TNF-α), and the risk of expected lung cancer. The study aimed at investigating the expression levels of mir-126 and mir-124, as well as TNF-α as possible biomarkers of expected smoking-related diseases. Methods: Twenty-five male smokers' age and sex-matched with 25 non-smokers were recruited for the present study. Plasma expression levels of mir-126 and mir-124 were evaluated using quantitative real-time PCR. Lipid profile, TNF-α, interleukin-6 and C-reactive protein were assessed in plasma of each participant. Results: Plasma miR-126 was statistically down-regulated in smokers relative to non-smokers; however, mir-124 did not show any significant changes between groups. Among the measured parameters, mir-126 and tumour necrosis factor alpha (TNF-α) displayed a good discrimination and sensitivity between smokers and non-smokers (AUC = 0.809 (95% CI: 0.668–0.95; p < 0.001) and 0.742(95% CI: 0.584–0.9; p < 0.01), respectively. Also, the combined evaluation of miR-126 and TNF-α levels showed high discrimination (AUC= 0.889 (95% CI: 0.779–1.00; p < 0.0001), sensitivity = 85%, and specificity = 80% in the diagnosis of smokers with non-smokers. Conclusions: MiR-126 and TNF-α are potential biomarkers of smoking-related diseases and are important in assessing the expected tobacco-related harm.